Selection of functional single domain antibody fragments for interfering with protein-protein interactions inside cells: a "one plasmid" mammalian two-hybrid system. - Tanaka, T; Rabbitts, T (2012)
As a complement to the intracellular antibody capture method to isolate intracellular single domain antibody fragments (iDabs) from high diverse libraries, we describe here a simple mammalian two-hybrid (M2H) protocol using a "bait-prey hybrid single plasmid" to assess those interfering iDabs that will block protein-protein interactions of a target with its natural partner proteins. This rapid method identifies interfering iDabs in one step and improves the reproducibility of the results between experiments and samples (e.g., different single domain antibody clones) compared to traditional M2H. This method yields functional, interfering iDabs and can be applied to any interfering molecule for use as a research tool or template for clinical inhibitor production.